A CRITICAL APPRAISAL OF COVID-19 IN INDIA - Das, Dr Pradip Kumar (Archives of Business Research, 2020)
COVID-19 virus causes respiratory problems including pneumonia, cold, sneezing and coughing, and transmits human to human or human to animal via airborne droplets. World Health Organization advises to avoid public gatherings and close contact to infected persons and pet animals. India has made several precautionary measures to mitigate the disease at the initial stage. However, the density of population in India makes it difficult to control the disease, if government does not incorporate the visionary strategies. Since attacked several nations have been worried for their people lives, developing country like India with huge population should consider about the livelihood of the people belonging to below poverty line or BPL equally with other life. This paper will give insights to make effective strategy to culminate the world threat COVID-19 in India. Keywords: COVID-19; India; Healthcare; Strategies; Community hospital.